Pengaruh Kualitas Produk, Harga Dan Lokasi Terhadap Keputusan Pembelian (Studi Pada Kafe Es Teh Indonesia Tlogomas Kota Malang) - Abd Halim; Abdul Kodir Djaelani; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to test and explain Teh effect of product quality , price and location, on Teh purchasing decision of Teh study on Indonesian Iced Tea Outlet in Tlogomas Malang. This type is explanatory research with a quantitative approach. Teh data analysis method use is multiple linear regression. Teh sampling technique used in this study was purposive sampling with a total sample of 80 respondents. To solve Teh problems in this study using Teh help of SPSS with validity tests, reliability tests, normality tests, multicollinearity tests, hateroskedasticity tests, multiple linear regression analysis, f tests (simultaneous, t tests (partial). Teh results of this study show that simultaneously Teh variables of product quality , price, and location have an effect to purchasing decisions . And Tehre is a partial influence between product quality, price, and location variables on purchasing decisions. Keywords: Product Quality , Price, Location, Purchasing decision.